2016
DOI: 10.5815/ijitcs.2016.03.10
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Software Tool to Generate Customer Needs for Effective Design of Online Shopping Websites

Abstract: Abstract-Effective design of online shopping websites is the need of the hour as design plays a crucial role in the success of online shopping businesses. Recently, the use of Quality Function Deployment (QFD) has been reported for the design of online shopping websites. QFD is a customer driven process that encompasses voluminous data gathered from customers through several techniques like personal interview, focus groups, surveys etc. This massive, unsorted and unstructured data is required to be transformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…QFD is one strong decision-making tool that has been utilized in varied areas. 57,58 The use of QFD as a decision support tool has been reported by many researchers. A QFD-driven decision support system could also be explored and can be employed to serve the purpose.…”
Section: Depression Detection From Video Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…QFD is one strong decision-making tool that has been utilized in varied areas. 57,58 The use of QFD as a decision support tool has been reported by many researchers. A QFD-driven decision support system could also be explored and can be employed to serve the purpose.…”
Section: Depression Detection From Video Featuresmentioning
confidence: 99%
“…Based on novel characteristics derived from facial expression geometry and vocabulary, by decoding non‐verbal signs of depression, a device with the capacity to function as a decision support system is proposed. QFD is one strong decision‐making tool that has been utilized in varied areas 57,58 . The use of QFD as a decision support tool has been reported by many researchers.…”
Section: Classification Of Depression Detection Techniquesmentioning
confidence: 99%
“…Quality Function Deployment (QFD) is one such decision making tool that can serve the purpose well. The use of QFD as a decision support tool has been demonstrated by 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…The use of QFD as a decision support tool has been demonstrated by. 17,18 This research explores related research works that have presented a method for identifying depression in the public media as well as several pre-trained models on text, which are discussed in Section 2. The dataset used for the experiment is discussed in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Quality function deployment is one tool that has been utilized widely in various applications areas. Some of the works depicting it as strong decision-making tool are reported by Sharma et al [2][3][4] In addition, CPS systems are found utilized in application areas such as robots, medical devices, and intelligent buildings. Such CPS systems are utilized with hybridized ESVM-enhanced-support vector machine with enhanced Ada-Boost algorithm for classification for the detection of intrusion and fault classifications relying on TE-dataset.…”
Section: Introductionmentioning
confidence: 99%